«VUZECOFEST» AS A PRACTICE OF ECOLOGICAL CULTURE DEVELOPMENT AMONG STUDENTS - A. I. Evseeva (Moscow Polytechnic University, 2018)
One of the tasks, for transition to sustainable development, is the formation of a new culture of relationships between people and the environment - the culture of eco-friendly lifestyle. Being one of the main institutions for socialization of youth, universities play a leading role in this process. Involvement of students and university staff in the implementation of ecological projects in the framework of extracurricular work can encourage the formation of eco-friendly culture. The implementation of such projects not only contributes to overall greening of education, but also forms appropriate skills and habits of eco-friendly lifestyle among a wide range of people. The article focuses on the main directions of greening of universities, introduces the foreign experience of "green campus", and represents the experience of implementing student projects in the field of ecology and sustainable development in Russian universities. Particular emphasis is placed on the opportunities and benefits of greening Russian universities by supporting and developing student initiatives. Interuniversity festival «VuzEcoFest» is the example of student initiatives in the sphere of ecology. It is a youth project for the promotion of conception of green universities.